2020
DOI: 10.1055/s-0040-1719211
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress during COVID-19 Lockdown among Dental Students and Practitioners in India: A Cross-Sectional Survey

Abstract: Objective In response to the coronavirus disease 2019 (COVID-19) pandemic, the Indian Government imposed a countrywide lockdown of 21 days from March 25 to April 14, 2020, which was further extended to 60 days. The sudden draconian measures changed the delivery of dental education and practice throughout the country. The study aimed to screen for depression during the COVID-19 lockdown and the factors associated with it among dental students and practitioners in highly COVID-19 infected states of India. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 18 publications
3
57
3
1
Order By: Relevance
“…In this study, the findings revealed that males were more likely to have depressive, anxiety, insomnia, and fear symptoms than female students. A recent online cross-sectional survey performed in Delhi NCR, Maharashtra, and Tamil Nadu during May 2020 investigated 335 dental students and practitioners who used PHQ-9 scores found that those who were depressed were likely to be male than female (42). However, the result of this study was consistent with the other research conducted in China that male students were significantly more anxious than female students (43).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, the findings revealed that males were more likely to have depressive, anxiety, insomnia, and fear symptoms than female students. A recent online cross-sectional survey performed in Delhi NCR, Maharashtra, and Tamil Nadu during May 2020 investigated 335 dental students and practitioners who used PHQ-9 scores found that those who were depressed were likely to be male than female (42). However, the result of this study was consistent with the other research conducted in China that male students were significantly more anxious than female students (43).…”
Section: Discussionsupporting
confidence: 85%
“…Many studies found that young students were at higher risks of general psychiatric disorders, stress, anxiety, depression, loneliness, psychological distress, suicidal ideation, insomnia, and post-traumatic stress symptoms (46)(47)(48)(49). A recent cross-sectional survey performed in India during May 2020 investigated 335 dental students and practitioners who used PHQ-9 scores and found that those who were depressed were likely to be younger than 30 years old (42).…”
Section: Discussionmentioning
confidence: 99%
“…Such outcomes may support the study conducted by Gasparro et al (2020), which underlined that young dentists with fewer years of work experience had higher levels of depressive symptoms. Furthermore, Chakraborty et al (2020) highlighted that significant level of depression was seen among young dental practitioners, who found it difficult to meet clinics and living expenses during the lockdown. Such economic uncertainty, together with the uncertainty about one's own job and the future in general, may result in serious psychopathological symptoms such as depression (Godinic, Obrenovic, & Khudaykulov, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Gasparro et al (2020), revealed that dentists with low fear of COVID -19 had weaker perceived job insecurity and depressive symptoms, compared to their colleagues who displayed higher fear to COVID -19. Furthermore, Chakraborty et al (2020) and Gasparro et al (2020) found that young dentists with fewer years of work experience were associated with higher levels of depressive symptoms.…”
Section: Theme 3: Perceived Job Insecurity and Loss Of Incomementioning
confidence: 99%
“…The present study evaluated the effect of yoga on the quality of life of oral healthcare professionals during the COVID 19 pandemic . In a previous study 12 carried out in India, high level of depression was observed in significant number of dental students and practitioners and the authors emphasized the importance of monitoring and addressing the mental health needs of these professionals during and after the lockdown.…”
Section: Discussionmentioning
confidence: 99%